2014
DOI: 10.1590/s1516-14392014005000040
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of fatigue lives of fly ash modified dense bituminous mixtures based on artificial neural networks

Abstract: This study deals with estimation of fatigue lives of bituminous mixtures using artificial neural networks. Different types of fly ash were used as filler replacing agents in a dense bituminous mixture. Fatigue tests were performed using repeated load indirect tensile test apparatus under controlled stress conditions. For determination of fatigue life, the initiation of macro crack was accepted as the main criteria to terminate the test. The full-scale tests on asphalt pavement sections are very expensive and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Composite Al Assaf and El Kadi, 12 Bezazi et al, 13 Salmalian et al, 14 Salmalian et al, 16 Rohman et al, 18 Aymerich and Serra, 21 Junior et al, 26 Vassilopoulos et al, 28 Mathur et al, 29 Cai et al, 30 Liao et al, 31 Al-Assadi et al, 32 Kumar et al, 33 Uygur et al, 41 Xiang et al, 42 Vadood et al, 43 Al-Assaf, and El Kadi, 53 Vassilopoulos et al, 55 Xiao et al, 59 Al-Assadi et al, 61 El Kadi, 62 Tapkin, 68 Moghaddam et al, 69 Yan et al, 72 El Kadi and Al-Assaf, 74 El Kadi and Al-Assaf, 77 Lee et al, 78 Deveci and Artem, 95 Vassilopoulos et al, 100 Azarhoosh et al, 102 Ertas, 111 Ertas and Sonmez, 117 Ertas and Sonmez, 118 El Kadi et al, 125 Deveci and Artem 130 and Sai et al 131 Alloys Figueira Pujol and Andrade Pinto, 15 Susmikanti, 17 Venkatesh and Rack, 22 Pleune and Chopra, 23 Sohn and Bae, 24 Genel, 25 Marquardt and Zenner, 27 Zhaohua, 35 Xu et al,…”
Section: Materials Publicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Composite Al Assaf and El Kadi, 12 Bezazi et al, 13 Salmalian et al, 14 Salmalian et al, 16 Rohman et al, 18 Aymerich and Serra, 21 Junior et al, 26 Vassilopoulos et al, 28 Mathur et al, 29 Cai et al, 30 Liao et al, 31 Al-Assadi et al, 32 Kumar et al, 33 Uygur et al, 41 Xiang et al, 42 Vadood et al, 43 Al-Assaf, and El Kadi, 53 Vassilopoulos et al, 55 Xiao et al, 59 Al-Assadi et al, 61 El Kadi, 62 Tapkin, 68 Moghaddam et al, 69 Yan et al, 72 El Kadi and Al-Assaf, 74 El Kadi and Al-Assaf, 77 Lee et al, 78 Deveci and Artem, 95 Vassilopoulos et al, 100 Azarhoosh et al, 102 Ertas, 111 Ertas and Sonmez, 117 Ertas and Sonmez, 118 El Kadi et al, 125 Deveci and Artem 130 and Sai et al 131 Alloys Figueira Pujol and Andrade Pinto, 15 Susmikanti, 17 Venkatesh and Rack, 22 Pleune and Chopra, 23 Sohn and Bae, 24 Genel, 25 Marquardt and Zenner, 27 Zhaohua, 35 Xu et al,…”
Section: Materials Publicationsmentioning
confidence: 99%
“…Activation function Sigmoid Figueira Pujol and Andrade Pinto, 15 Susmikanti, 17 Rohman et al, 18 Han, 20 Aymerich and Serra, 21 Sohn and Bae, 24 Genel, 25 Junior et al, 26 Vassilopoulos et al, 28 Liao et al, 31 Al-Assadi et al, 32 Kumar et al, 33 Yang et al, 39 Uygur et al, 41 Martinez and Ponce, 47 Barbosa et al, 48 Srinivasan et al, 52 Park and Kang, 54 Vassilopoulos et al, 55 Majidian and Saidi, 56 Xiao et al, 59 Al-Assadi et al, 61 Jin et al, 67 Tapkin, 68 Moghaddam et al, 69 Durodola et al, 70 Durodola et al, 71 Yang et al 73 and Ahmad et al 82…”
Section: Functional Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural networks are non-linear statistical data modelling tools. They can be used to model complex relationships between inputs and outputs or to find patterns in data (Haykin, 1999, Tapkin, 2010.…”
Section: Generalmentioning
confidence: 99%
“…Tapkin (Tapkin, 2010) The aim of another research (Xiao et al, 2010) was the application of ANN for predicting the penetration index of binders after long term aging. During the same study, ANN was compared to statistical regression models and it was found to predict the penetration index more accurately.…”
Section: Generalmentioning
confidence: 99%